Patterns of health service use and child abuse or neglect in young childhood: a systematic review. (4th April 2011) - Woodman, J; Brandon, M; Glaser, D; Gilbert, R
Abstract : Background: Evidence suggests that abused and neglected children have higher rates of healthcare need than non-abused or neglected children. Higher healthcare need should result in more frequent use of healthcare services. However, there is growing evidence that abused or neglected children do not attend emergency departments more frequently than other similar children. Understanding patterns of healthcare use among abused or neglected children is important for resource allocation, identifying unmet need and generating hypotheses about which services might be best placed to support abused or neglected children. Aim: This systematic review investigated associations between patterns of health service use and child abuse or neglect in young childhood. Methods: We searched six databases (ASSIA, CINAHL, Medline, Social Science Index and Social Science Citation Index), two journals and reference lists. We included studies in English (post-1989) which reported universal, specialist and emergency health service use by children <13 years in developed countries, stratified by abuse or neglect status. We appraised quality using EPIQ. Results: We included 15 primary studies and 1 review. Studies reported that abused or neglected children had increased risk of: multiple visits to primary care (OR: 1.7 to 2.1; 1 USA study); incomplete or inconsistent primary healthcare (OR/RR: 2.6 to 6.9; 2 USA studies); hospital admissions (RR: 1.49 to 2.09; 1 Australian study); and contact with mental health services (OR/RR: 1.6 to 5.0; 4 USA studies, 1 Italian, 1 Canadian, 1 UK). There were mixed results for emergency services (five studies) and services for ear/eyes/speech or chronic conditions/disability (two studies). 12 studies were poor quality. Conclusions: There was good evidence that child abuse and neglect were associated with more frequent but inconsistent/incomplete primary care use and higher rates of admissions. There was only weak evidence of associations for other services, once confounding factors were taken into account. Positive associations were neither strong nor specific enough for health service use to be a useful marker of child abuse or neglect. As healthcare need is higher in abused and neglected children, lack of a strong association could imply unmet need. Future research should assess unmet need.